2004
DOI: 10.1002/bit.20198
|View full text |Cite
|
Sign up to set email alerts
|

Real time quantitative PCR as a method to evaluate xenotropic murine leukemia virus removal during pharmaceutical protein purification

Abstract: Chinese hamster ovary cells used for pharmaceutical protein production express noninfectious retrovirus-like particles. To assure the safety of pharmaceutical proteins, validation of the ability of manufacturing processes to clear retrovirus-like particles is required for product registration. Xenotropic murine leukemia virus (X-MuLV) is often used as a model virus for clearance studies. Traditionally, cell-based infectivity assay has been the standard virus quantification method. In this article, a real time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Extraction of viral genomic material was then performed using either the EZ1 Virus Mini Kit v2.0 on a BioRobot EZ1 (Qiagen, Inc., Valencia, CA) or the MagAttract Virus Mini Kit v1.3 on a BioRobot M48 (Qiagen, Inc.). The QPCR assays used to quantify X-MuLV, SV40, and MMV VP were performed as previously described (Shi et al, 1999a(Shi et al, , 2004Zhan et al, 2002). For viral clearance studies, sample interference was determined by comparing 1:10 diluted samples with undiluted samples.…”
Section: Real-time Quantitative Pcr (Qpcr) Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of viral genomic material was then performed using either the EZ1 Virus Mini Kit v2.0 on a BioRobot EZ1 (Qiagen, Inc., Valencia, CA) or the MagAttract Virus Mini Kit v1.3 on a BioRobot M48 (Qiagen, Inc.). The QPCR assays used to quantify X-MuLV, SV40, and MMV VP were performed as previously described (Shi et al, 1999a(Shi et al, , 2004Zhan et al, 2002). For viral clearance studies, sample interference was determined by comparing 1:10 diluted samples with undiluted samples.…”
Section: Real-time Quantitative Pcr (Qpcr) Assaysmentioning
confidence: 99%
“…In addition to the virus purification literature, there are also published reports describing viral clearance using QSFF resin (Curtis et al, 2003;Norling et al, 2005;Shi et al, 1999bShi et al, , 2004Strauss et al, 2009;Valera et al, 2003). Although most of these do not describe much characterization of the processes used, a few have demonstrated that salt concentration (or conductivity), salt composition, and pH are important factors for viral clearance (Curtis et al, 2003;Strauss et al, 2009).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The validation studies are typically scaled-down spiking studies using model viruses and production scale in-process intermediates. The virus clearance of individual purification unit operations, such as chromatography or virus filtration, is measured and expressed as a log 10 reduction value, or LRV (Brorson et al, 2004;Shi et al, 2004). The LRV of orthogonal steps (modules where clearance mechanisms differ) are added together to compute the overall process LRV for comparison to the quantity of endogenous retrovirus in the cell culture harvests.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] Current regulations require that the manufacturing process demonstrate the ability to clear model viruses to ensure the safety of these cell-linederived products prior to approval, with additional built-in safety for robustness. [42][43][44] AEX chromatography has been frequently applied as a viral clearance step during downstream processing, in addition to impurity clearance of molecular species such as HCP and DNA.…”
Section: Viral Clearance Using Adsorptive Hybrid Filtersmentioning
confidence: 99%